INDONESIAN EXPERIENCE IN DEALING WITH TRADEMARK LAW: CASE STUDY OF BATIK SMEs - Sardjono, Agus; Prastyo, Brian Amy; Larasati, Desrezka Gunti (UI Scholars Hub, 2013)
This research aims to observe whether the Trademark Law can contribute to protect Indonesia’s batik business, particularly for the small-medium enterprises who produce and sell batik products (“Batik SMEs”). The individual trademark system has not been successful to support the batik SMEs’ business. However, the fact that those SMEs gather in a community, organization, or kinships bring potentials for the development of collective trademarks, which can address the problems that individual trademark cannot anticipate. This research finds that, in order to anticipate the free-trade ‘attack,’ i.e. imported textiles with batik patterns/motifs; Indonesian batik SMEs need to be nurtured and encouraged to register their own collective trademarks, and to build their branding infrastructure, through local batik community’s standardization, and collective batik labeling. This recommendation is also proposed considering the government’s ineffective policy on Batikmark. This research will take samples of Batik SMEs in several areas, namely Yogyakarta, Pekalongan, Solo, and Jakarta. Those areas have been recalled as some of the centers for Batik production and trading activities. This research is conducted through combining the quantitative and qualitative-empirical methods. Data are collected through literature studies, interviews, as well as questionnaires, including site visits and discussions with the SMEs in those areas.